1998
DOI: 10.1002/(sici)1096-8628(19981116)80:3<199::aid-ajmg3>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Combined trisomy 9 and Ullrich-Turner syndrome in a girl with a 46,X,der(9)t(X;9)(q12;q32) karyotype

Abstract: Total trisomy 9 is a rare disorder with most patients dying before age 4 months. Herein, we report a 9-year-old girl with mental retardation, short stature, a peculiar face and other minor defects, who was diagnosed as having an unbalanced de novo X-autosome translocation with a 46,X,der(9)t(X;9)(q12;q32) karyotype resulting in almost a full trisomy 9(pter-->q32) and a partial monosomy X(q12-->pter). The clinical findings of our patient, almost exclusively resemble those of trisomy 9p and the Ullrich-Turner sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Indeed, there are many cases in which the attenuated phenotype of individuals trisomic for a segment of autosome, translocated onto an inactive X, appears to be correlated well with the spreading of late replication into it (Canun et al 1998;Disteche et al 1984;Keitges and Palmer 1986;Mohandas et al 1982;Williams and Dear 1987). Such cases imply that the inactivated region of autosome can be defined by the extent of spread of late replication.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are many cases in which the attenuated phenotype of individuals trisomic for a segment of autosome, translocated onto an inactive X, appears to be correlated well with the spreading of late replication into it (Canun et al 1998;Disteche et al 1984;Keitges and Palmer 1986;Mohandas et al 1982;Williams and Dear 1987). Such cases imply that the inactivated region of autosome can be defined by the extent of spread of late replication.…”
Section: Discussionmentioning
confidence: 99%
“…Spreading of XIST RNA into the translocated autosomal segment appears to be a plausible mechanism for autosomal gene silencing. However, cytogenetic and molecular studies show incomplete or discontinuous XIST RNA spreading and either limited or even absence of a correlation between late replication of autosomal material and gene silencing in cells from patients with an attenuated phenotype [Keitges and Palmer, 1986; Schanz and Steinbach, 1989; Bettio et al, 1994; Kulharya et al, 1995; Garcia‐Heras et al, 1997; Canún et al, 1998; Bacino et al, 1999; Blennow and Sahlén, 1999; Duthie et al, 1999; Keohane et al, 1999; Abuelo et al, 2000; Sharp et al, 2001, 2002; Waters et al, 2001; Hall et al, 2002; Gläser et al, 2004; Panasiuk et al, 2004; Yatsenko et al, 2004]. It has been suggested that autosomal chromatin lacks some features necessary for spreading and maintenance of X inactivation [Keohane et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…In any event, these active genes apparently have not adversely affected their patient's phenotype. Other recent reports in which partial autosomal trisomies resulting from X‐chromosome translocations have resulted in mild phenotypes include partial trisomy 3p [Bettio et al, 1994; Kulharya et al, 1995], partial trisomy 9 [Canún et al, 1998], partial trisomy 16q (Bacino et al, [1999], and partial trisomy 13q [Blennow and Sahlén, 1999]. In the latter case, the researchers thought their patient had been “rescued” from the effects of trisomy 13q by the effects of skewed inactivation.…”
Section: Discussionmentioning
confidence: 98%